Possibilities for Multispecies Approaches in Coffee Landscapes - Jose Ramon Becerra Vera (Ethnobiology Letters, 2021)
Multispecies approaches can increase our knowledge around the social and ecological dimensions of coffee landscapes. Ethnobiologists combine the social and natural sciences to study the relationships between humans, the environment, and biota. Multispecies approaches can build from these strategies to further explore the social and biological elements that humans together with more-than-humans contribute to ecological landscapes. Using co-constitutions as a key concept, I highlight multispecies studies into agrarian worlds, review ethnobiological studies around coffee, and suggest potential research areas.